Yellow wife : [large type] a novel - Johnson, Sadeqa (Center Point Large Print, 2021)
Born on a plantation but set apart from the others by her mother's position as a medicine woman, a young slave is forced to leave home at eighteen and unexpectedly finds herself in an infamously cruel jail.